Kontribusi Sektor Ketenagakerjaan Terhadap Pembentukan Struktur Ekonomi Daerah Provinsi Jawa Tengah - Nugroho, Yorizal Ananto, Muhammad Arif, SE, M.Ec, Dev (2016)
Regional economic growth is reflected in the GDP per capita. When GDP growth and the GDP per capita is high, it means that there are more chances of better employment and higher income level which is obtained. A skilled and educated labor is a requirement to create positive economic growth, which the quality of the labor must be equipped with proper education and relevant with the needs of the labor itself. This study aimed to analyze the effect of the employment sector to the GDP of Central Java province Years 2011-2014. The dependent variable of this study is in the form of the GDP of Central Java Province (GDP), while the independent variables of this study are Unemployment Rate (TPT), Level UMK (UMK), Public Education Level of Working Age (EducationLevel) and Open Development Index (HDI). This study uses secondary data with panel data regression analysis techniques. The results showed that the Fixed Effects Model (FEM) is the most appropiate panel data regression model. Based on test validity or the effect of t test, level of education had no significant effect to the GDP, while the unemployment rate significantly and negatively influences the GDP. On the other hand, UMK and human development index has significant positive effect on the GDP. Based on the F test, the Unemployment Rate, UMK, education level and IPM significantly influence the GDP of Central Java province.